Criminal Justice Involvement and Employment Outcomes Among Women - Sheely, Amanda (Crime & delinquency, 2020)
This article investigates the potentially cumulative effects of being arrested, convicted, and incarcerated on labor market outcomes among women, as well as whether decreased employment levels are due to labor market exclusion or detachment. Using data from the National Longitudinal Survey of Youth 1997, I find that arrested women have reduced levels of employment, due to both labor market exclusion (unemployment) and labor market detachment (not in the labor force). Once the effect of being arrested is taken into account, women who are convicted or incarcerated do not face any additional negative employment consequences. These results demonstrate that policymakers must look beyond incarceration to reduce the impact of criminal justice involvement on women.